The Role of Gakkumdu Bawaslu East Jakarta In Law Enforcement of Election Crimes - Rahmat, Diding; Sujono, Sujono; Sudarto, Sudarto; Farhani, Athari (Jurnal Cita Hukum, 2025)
Law enforcement of election crimes is a critical aspect to ensure the creation of a fair and transparent democratic process. This research discusses the role of Gakkumdu Bawaslu East Jakarta in enforcing the law on election crimes. Gakkumdu Bawaslu East Jakarta is responsible for handling and resolving cases of election law violations, which include administrative violations, code of ethics violations, and election crimes. This research identifies how the East Jakarta Bawaslu Gakkumdu functions in preventing and enforcing the law against election violations and the challenges faced in carrying out this task. The methodology used involves qualitative secondary data analysis, including documents, reports and interviews with related parties. The research results show that the East Jakarta Gakkumdu Bawaslu plays a crucial role in enforcing compliance with election regulations, despite several obstacles in carrying out its duties, such as limited resources and coordination between institutions. This research suggests several corrective steps to increase the effectiveness of Gakkumdu in enforcing election law in the future.